Subglacial processes on an Antarctic ice stream bed. 2 : Can modelled ice dynamics explain the morphology of mega-scale glacial lineations? - Jamieson, Stewart S. R.; Stokes, Chris R.; Livingstone, Stephen J.; Vieli, Andreas; Cofaigh, Colm Ó; Hillenbrand, Claus-Dieter; Spagnolo, Matteo (Journal of Glaciology, 2016)
ACKNOWLEDGEMENTS This work was funded by Natural Environmental Research Council (NERC) UK standard grants NE/G015430/1 and NE/G018677/1. Jamieson was supported by NERC Fellowship NE/J018333/1 and Spagnolo was supported by NERC new investigator grant NE/J004766/1. This research would not have been possible without the hard work of scientists and crew during research cruises JR59, JR71, JR157 and NBP0201. We thank Chris Clark for useful discussions and two anonymous reviewers for comments that helped to improve the manuscript. Data produced in this manuscript are available from the corresponding author. Peer reviewed